Model Pembelajaran Luring pada Masa Pandemi Covid-19 di Raudhatul Atfal - Fatmasari Fatmasari; Sri Hartati (Jurnal Family Education, 2022)
This study aims to determine the implementation of the offine learning model during the Covid-19 pandemic in Raudhatul Atfal Darul Ulum, Koto VII District, Sijunjung regency. This research is descriptive using qualitative data. Al of inside data was obtained through a series of in-depth interviews withinformants,. The informants in this study were the B1 class teacher and the B2 class teacher Raudhatul Atfal Darul Ulum, Koto VII District, Sijunjung regency. The coming colection technique used in this research is in the form of observation, documentation and interviews. The findings in this study are the implementetion of thr Raudhatul Atfal Darul Ulum offline learning model during the Covid-19 pandemic by applying health protocols both in pre-learning, during learningand aftar learning in accordanc with the health protocols implemented by the cntral govermment and local govermmensts